Experimental modeling of antimony sulfides-rich geothermal deposits and their solubility in the presence of polymeric antiscalants. (September 2022) - Karaburun, Emre; Sozen, Yigit; Çiftçi, Celal; Sahin, Hasan; Baba, Alper; Akbey, Ümit; Yeşilnacar, Mehmet İrfan and Erdim, Eray and Regenspurg, Simona and Demir, Mustafa M.
Highlights: Sb-containing sulfide and oxide deposits were artificially obtained. Solubility of the bulk geothermal deposits is achieved in alkaline Na2 S solution. The performance of various antiscalants was investigated for the artificial deposits. Binding energy between functional groups and the Sb n+ and S 2− ions was calculated. Sulfonic acid containing antiscalants were found to be effective. Abstract: Antimony (Sb)-rich geothermal deposits have been observed in many geothermal power plants worldwide. They occur as red-colored, sulfidic precipitates disturbing energy-harvesting by clogging the geothermal installations. In order to prevent the formation of this scale, information on its physicochemical features is needed. For this purpose, Sb-rich sulfide-based deposits were synthesized at controlled conditions in a pressurized glass reactor at geothermal conditions (135 °C and 3.5 bar). Various polymeric antiscalants with different functional groups, such as acrylic acid, sulphonic acid, and phosphonic acid groups were tested for their effect on Sb sulfide solubility. An additional computational study was performed to determine the binding energy of Sb and S atoms to these groups. The results suggest that sulfonic acid groups are the most affective. Therefore, it was concluded that these macromolecule containing sulfonic acid groups and poly (vinyl sulfonic acid) derivatives could potentially act as antiscalants for the formation of antimony sulfide.